Information Theory Adapted to Wide Range of Scientific Activity - William L. Carpenter (Journal of Applied Communications, 1969)
Claude Shannon, Bell Telephone Co. engineer and mathematician, set in motion a chain of events in a wide variety of scientific disciplines when he revealed his theoretical communications framework at the end of World War II.